Financial Performance Mediation in the Influence of Islamic Corporate Governance Disclosure on the Islamic Social Reporting - Ichsan Setiyo Budi; Rahmawati Rahmawati; Falikhatun Falikhatun; Muthmainah Muthmainah; Ardi Gunardi (Indonesian Journal of Sustainability Accounting and Management, 2019)
The results of the research on the social role of Islamic banks show inconsistency both domestically and abroad; this is the basis for conducting this research to re-explain the Islamic Corporate Governance (ICG) and Islamic Social Reporting (ISR) relationship, models. This study aims to examine the indirect effect of ICG disclosure on ISR disclosure with financial performance as a mediating variable in Islamic Banking in Indonesia. This study uses secondary data with annual report data sources and financial statements on Islamic banking in Indonesia. They are testing this study using stepwise regression analysis with data for the annual reporting period of 2011 through 2014. The result that financial performance mediates the effect of disclosure of ICG on ISR; this shows that proper management of Islamic banks will produce high financial performance so that they can carry out their social roles well too. The contribution of this study is to develop a new model of the part of financial performance mediating the effect of ICG disclosure on ISR so that it is beneficial for the development of science.